2008
DOI: 10.1002/pbc.21344
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central venous catheters are a good option for prolonged venous access in children with cancer

Abstract: We found PICC to be a convenient, cheap, safe, and reliable device for long term intravenous access in children with malignancies. This was possible with the help of dedicated catheter care nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 26 publications
4
44
3
5
Order By: Relevance
“…Previous 5 studies reported that the catheter life of PICCs in adults or children suffering from cancer were from 13 to 246 days [5][6][7][8][9]. The comparison among recent reports and our present study is shown in Table 4 [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Previous 5 studies reported that the catheter life of PICCs in adults or children suffering from cancer were from 13 to 246 days [5][6][7][8][9]. The comparison among recent reports and our present study is shown in Table 4 [5][6][7][8][9].…”
Section: Discussionsupporting
confidence: 46%
“…Especially, median age of our study was the highest among those of the reports on children, which might lead rather long catheter life in our study. In a different point of view, we got rather long catheter life with BD First PICCs, which had been thought to have a higher risk of occlusion than Bard Groshong PICCs [5][6][7][8][9]. At least, it was mentioned that more than four-fifths of PICCs could be used until the completion of the therapy or death without removal due to complications.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Peripherally inserted central venous catheter (PICC) has been demonstrated to be an outstanding tool for providing long-term intravascular access in oncology patients [1,2]. It has also been shown that the complication rate in cancer patients appears to be higher than that in other patients probably due to immunocompromise and prothrombotic tendency [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that the common causes for catheter removal were suspected infection, dislodgement, phlebitis, and occlusion with the rates of 1.27, 0.31, 0.06, and 0.06 per 1,000 catheter days, respectively. [5] A study was conducted to examine the impact of implementation of guidelines for the management of peripheral intravascular devices on nurses' knowledge and practice as well as patient outcome in a Hong Kong tertiary care teaching hospital. The results showed that there is decrease in the incidence of extravasations and phlebitis with significant improvement in practice.…”
Section: Review Of Literaturementioning
confidence: 99%